Problem-Based Learning: Validation of an assessment instrument - Petra Micu, Ileana (2000)
OBJECTIVES: To analyze the labour of a multidisciplinary work group in preparing of an instrument for asssessing the performance of students during work sessions of the teaching strategy tenned ProblemBased Leming (PBL), as well some methods useful for previos assessment of instrument and its results, in order to prepare the questionnaire for its statistical assessment. MATERIALS AND METHODS: Four critical areas were taken into account: Characteristics and organization of both the work group and the instrument to be prepared, appearance validity or content validity, clarity validity, and the labour of the group after the factorial analysis. RESULTS AND CONCLUSIONS: A work group for development of an academic assessment instrument must include people willing to team-working and coordinators expert in this field; enough time, new skills development and thoroughly reviews are required for achieving a practical and valide instrument; as well the usefulness of the labour can be demostrated through the emerging reactives quality and reduced number of reactives to be eliminated.